Governance that transforms: Governance strategies for micro, small, and medium enterprises in Pernambuco - Moura, Giselly Fernanda Lima de; Maciel, Shyrleide Leite Menezes; Souza Ramos, Raquel; Florencio dos Santos, Joséte (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: This article aims to analyze the governance practices adopted by small businesses that make up the Local Productive Arrangement of Clothing in the Agreste region of Pernambuco. Methodology/approach: This is a quantitative and descriptive study, conducted in 33 companies from the clothing, laundry, and textile sectors. Data were collected through a structured questionnaire with a Likert scale and analyzed using Microsoft Excel and the SPSS software, version 20.0. Originality/Relevance: Although the companies adopt governance practices, there are indications that these practices need to be further developed and adopted by a greater number of companies, which happens due to limited resources. Key findings: The results show that companies adopt practices of transparency and elements of environmental and social responsibility, bringing strategic benefits to the organization. The organizations value corporate governance practices. There is an adoption of transparency with suppliers, banks, partners, and the government, which can bring benefits to the organization, such as facilitating the acquisition of external resources. Finally, despite the existence of governance practices within the institutions, they need to invest more in this area. Theoretical/methodological contributions: Academically, the results expand the knowledge on governance in MSMEs in the Brazilian context in the Local Productive Arrangement of Clothing in the Agreste region of Pernambuco, highlighting the relevance of governance practices in these companies. Additionally, the findings also contributed to the literature by highlighting the opportunities and challenges of this sector in the regional context.